Digital spatial cracking behaviors of fine‐grained sandstone with precracks under uniaxial compression. (2nd July 2020) - Zhou, Xiao‐Ping; Zhao, Zhi; Liu, Yang
Summary: X‐ray computed tomography (CT) imaging and digital image correlation techniques are applied to study spatial cracking behaviors of sandstone under uniaxial compression, in which the angle between precracks is 45°, 90°, and 135° and the crack depth is 7.5 mm and 10 mm, respectively. Layered anisotropy damages and spatial cracking evolution are quantitatively analyzed by the defined digital layered anisotropy index and digital damage ratio, respectively. Three cases with different array of precracks evidence the depth effects of precracks on spatial crack propagation. Results show that the failure process of samples is first controlled by the coalescence of surface cracks in 2D space and then the samples are failed by the propagation of coalesced cracks (shear cracks with different shapes). The crack types for samples with precrack depth of 7.5 mm are all shear cracks for Cases 1‑3. Nevertheless, the crack types for samples with precrack depth of 10 mm are, respectively, the half X‐shape crack for Case 1, X‐shape crack for Case 2, and double shell crack for Case 3. The precrack has a significant promotion effect on the failure process when the angle between the two precracks is β = 90°, and the precrack has little to no effect on the failure process when the angle between the two precracks is β = 135°. As the depth of precrack increases to 10 mm, the crack types are changed in this study. The peak strength of sample subjected to uniaxial compression decreases with increasing depth of precracks, implying the decrease of the rock strength by the discontinuity.